Use of biomarkers in planning prosthetic rehabilitation in patients with periodontium tissues disorders - Romaniuk, V. N.; Voznyi, O. V.; Pavlov, S. V.; Романюк, Віктор Миколайович; Возний, Олександр Вікторович; Павлов, Сергій Васильович (publishing center of the ESCBM, The Czech Republic, 2018)
According to WHO, about 75 % of population in different regions of the world suffer from partial adentia. Clinical observations demonstrate that in the majority of cases the cause of adentia is generalized periodontitis which is an inflammatory and destructive disease of periodontium tissues that is characterized by inflammation of gums, formation of periodontal pockets and progressing destruction of alveolar ridge which requires dental implantation and prosthetic rehabilitation.[1] Periodontitis is considered one of the most globally spread diseases, with the incidence of 15-20 %. [2] Moreover, periodontitis is connected to other serious diseases such as ischemic heart disease, head and neck carcinoma, and chronic obstructive pulmonary disease. [3-5] At present there are no standard criteria for prosthetic treatment efficacy. In practical work, only functional and aesthetic properties of dentures are estimated which gives their general characteristics alone. Present methods of more detailed estimation of dentures and their impact of periodontium tissues (electromyography, Doppler sonography, rheography, polarography,functional tests) are still under investigation and do not allow to use them in practical sphere. At the same time, the estimation of the prospective results of prosthetic rehabilitation and the analysis of complications, connected with implanting and teeth replacement, allow to assess risk factors, typical of different kinds of dental prostheses, to justify reasonability of their employment and to predict treatment results. In the context of the mentioned above data, there is strong necessity in the introduction of new enlightening, minimally invasive, practically applicable methods of estimation of denture base condition at planning implantological treatment and estimating the efficacy of the performed prosthetic rehabilitation.
Keywords: тези доповідей; periodontitis; MMP-8; lactoferrin; cathelicidin; prosthetic rehabilitation